Weichselian stratigraphy, geomorphology and glacial dynamics in southern Finnish Lapland - P. Sarala (Bulletin of the Geological Society of Finland, 2005)
Quaternary stratigraphy and geomorphology were investigated by using aerial photo interpretation, digital elevation models and stratigraphical studies in southern Finnish Lapland. The development of glacial morphology was examined by reconstructing glacial flow patterns and subglacial conditions with emphasis on glacial dynamics. By comparing the climate history and available chronological data the ice-sheet development during the Weichselian was modelled in the area. Also, the Quaternary lithostratigraphy with descriptions, formal names and type sections of the Peräpohja Group was proposed. Glacial morphology with clear indication of glacial flow directions represents two Weichselian glacial advances in the area of southern Finnish Lapland. The older, northwest-southeast oriented glacial movement was seen as a drumlin field and was preserved under a later cold-based ice sheet. A west-east oriented landform assemblage of ribbed moraines, drumlins and flutings mainly indicated the younger glacial phase. Of the age of ice sheet development during the Weichselian two alternative interpretations have been presented: In the first model, the first glacial advance occurred during the Early Weichselian and was followed by interstadial about 85-74 ka ago. The Middle and Late Weichselian glaciation was continuously covering southern Finnish Lapland after that. The second model includes a new interpretation, in which the first glacial advance that reached the area is connected to the beginning of the Middle Weichselian. Ice-free interstadial occurred about 50-30 ka ago before the Late Weichselian glacial advance, when the Weichselian maximum was reached.